A Narrative Review of AI-Driven Omnichannel Branding Strategies in Global Digital Marketing - Satrio, Sello; Fatmawati, Yuli (Indonesian Scientific Publication, 2024)
This narrative review explores the evolution of brand communication strategies within the digital marketing ecosystem, emphasizing the growing significance of omnichannel approaches and emerging technologies in building consumer engagement and brand loyalty. The review aims to evaluate how integrated communication practices—especially those employing artificial intelligence (AI), data-driven personalization, and immersive technologies like virtual reality (VR)—redefine consumer-brand interactions. Literature was collected through comprehensive searches in Scopus and Google Scholar using a Boolean-based strategy with keywords such as